Implementation of Internet of Things (IoT) In Heart Rate Measurement Tool - Zhafira, Mutia; Sardi, Juli (Jurnal Teknik Elektro Indonesia, 2024)
The heart is one of the vital organs that plays an important role. Checking the condition of the heart is done by measuring the heart rate to find out whether it is beating normally or not as a first step to prevent heart disease. Therefore, this research aims to create an IoT-based heart rate monitor that is easy to use at any time. This research consists of making hardware which includes ESP32-C3, MAX30102 heart rate sensor, Beitian Bn-220 gps, 96''oled display and buzzer and software which includes Arduino IDE as system coding and Thinger.io platform as a medium for receiving and storing sensor data to facilitate a monitoring process. After testing, it was found that the average error of the MAX30102 heart rate sensor was 1.02%, and the difference between the distance of the coordinate points obtained by the Beitian gps with google maps was 3.79 metres indoors and 3.17 metres outdoors. Heart rate data and location points can also be stored in real time on Thinger.io and alerts can be received within 2 to 5 seconds. The results show that the system is working in line with the desired objectives.